Multilevel DC-link converter photovoltaic system with modified PSO based on maximum power point tracking. (1st September 2017) - Mao, Mingxuan; Zhang, Li; Duan, Qichang; Chong, Benjamin
Highlights: A modified particle swarm optimization based-MPPT method is proposed. Multilevel DC-link converter PV system is used to verify the proposed method. A PWM algorithm with permutation of PV sources is introduced. Simulations and comparisons of three MPPT methods are conducted. Abstract: The paper presents a modified particle swarm optimization (MPSO) control strategy for the maximum power point tracking applied to a multilevel DC-link PV power generation system. This system consists of a chain of PV modules with individual DC-DC converters and has a DC-AC converter at its terminals for generating AC voltage. The proposed MPSO control method can predict all PV voltages at their maximum power point on the basis of respective light level and temperature. A PWM with permutation of DC converter switching is applied to balance switch utilisation. The method is applied to a system of five-voltage levels with two PV-converter units under different light intensities and the results are compared with the perturb and observe (P&O) method and the traditional PSO method under the same operating conditions. The paper shows that the new method gives more rapid convergence, increased power output, and lower total harmonic distortion.